Wuling Si Penantang Pasar : Wujud Efektivitas Ekuitas Merek Dalam Mempengaruhi Keputusan Pembelian Konsumen - Muhamad Riski Miranto; Dwi Suryanto Hidayat (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2021)
This research was conducted with the aim of (1) analyzing the effect of brand association and perceived quality on brand equity, (2) knowing the effect of brand association, perceived quality and brand equity on purchasing decisions. (3) to determine the indirect effect of brand association and perceived quality on purchasing decisions through brand equity. A total of 100 respondents were taken as samples using snowball and accidental sampling. The data analysis technique used in this study was SEM-PLS with the help of SmartPLS version 3 software. The results showed that (1) brand association and perceived quality have a significant effect on brand equity. (2) brand association and brand equity have a positive and significant effect on purchasing decisions. (3) quality perceptions have no effect on purchasing decisions (4) Brand association and perceived quality have a positive and significant effect on purchasing decisions through brand equity.